CM-Pf deep brain stimulation and the long term management of motor and psychiatric symptoms in a case of Tourette syndrome. (April 2019) - Marano, Massimo; Migliore, Simone; Squitieri, Ferdinando; Insola, Angelo; Scarnati, Eugenio; Mazzone, Paolo
Highlights: Tourette syndrome is a rare neuropsychiatric disorder featured by chronic tics. Tourette is enriched of psychiatric comorbidities and could be refractory to medications. The thalamic CM-Pf complex is a promising deep brain stimulation target in Tourette. The CM-Pf is embedded in a network involving motor, associative and limbic structures. Patients receiving CM-Pf DBS should be studied also for psychiatric outcomes. Abstract: Tourette syndrome is a rare neuropsychiatric disorder affecting the cortico-striato-thalamo-cortical system. The disease manifests in childhood with tics and various psychiatric comorbidities. Cases of refractory Tourette syndrome are valuable candidates for functional neurosurgery. The thalamic centromedian-parafascicular complex is an experimental target that shows a promising role in Tourette syndrome deep brain stimulation, due to pathophysiologic evidences. We have shown on a long term follow-up, that thalamic deep brain stimulation, targeted on the centromedian-parafascicular complex, could modulate motor (i.e. tics) symptoms and owns a putative effect on various psychiatric aspects. Non-responding psychiatric symptoms could be due to the aberrant developmental environment of young Tourette patients more than disease itself. Centromedian-parafascicular complex is intriguingly embedded in motor, associative and limbic pathways and should be further investigated in his role for neuromodulation of human movement and behavior.